2021
DOI: 10.1093/cid/ciab732
|View full text |Cite
|
Sign up to set email alerts
|

Fostamatinib for the Treatment of Hospitalized Adults With Coronavirus Disease 2019: A Randomized Trial

Abstract: Background Coronavirus Disease 2019 (Covid-19) requiring hospitalization is characterized by robust antibody production, dysregulated immune response and immunothrombosis. Fostamatinib, is a novel spleen tyrosine kinase inhibitor we hypothesize will ameliorate Fc activation and attenuate harmful effects of the anti-COVID-19 immune response. Methods We conducted a double-blind, randomized, placebo-controlled trial in hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 24 publications
3
35
0
Order By: Relevance
“…Fostamatinib is a Tyrosine kinase inhibitor usually used to treat chronic immune thrombocytopenia ( 66 ). Studies support it for treatment of acute respiratory distress syndrome in COVID-19 ( 67 ) and a stage 2 clinical trial found it safe and showed evidence of better outcomes for COVID-19 patients compared to placebo, suggesting its standard use for care ( 68 ). In addition, PRIO (encoded by PRNP ) and MK12 (encoded by MAPK12 ) are both targeted by tetracyclines.…”
Section: Resultsmentioning
confidence: 99%
“…Fostamatinib is a Tyrosine kinase inhibitor usually used to treat chronic immune thrombocytopenia ( 66 ). Studies support it for treatment of acute respiratory distress syndrome in COVID-19 ( 67 ) and a stage 2 clinical trial found it safe and showed evidence of better outcomes for COVID-19 patients compared to placebo, suggesting its standard use for care ( 68 ). In addition, PRIO (encoded by PRNP ) and MK12 (encoded by MAPK12 ) are both targeted by tetracyclines.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, fostamatinib is being evaluated for efficacy and safety in COVID-19 subjects in multiple clinical studies (NCT04579393, NCT04629703). Results of Phase 2 study proved that the addition of fostamatinib was safe and effective for improving clinical outcomes ( Strich et al, 2021 ). The results of these clinical trials, which directly applied Fostamatinib to airway disorders, will be more valuable for clinical studies of fostamatinib or R406 in severe asthma in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Fostamatinib is also thought to be anti-inflammatory and potentially useful in COVID, independently of any platelet effects. 47 On the other hand, of all approved second-line agents for ITP, it may be the least tolerable. It increases blood pressure in most recipients and there are relatively frequent gastrointestinal effects, including nausea with very occasional vomiting and the development of diarrhea; 5% of patients may develop transaminitis.…”
Section: Section I a Young Female Patient With Immune Thrombocytopeni...mentioning
confidence: 99%
“…If not vaccinated prior to starting rituximab, need to wait to be vaccinated until 6-12 months after completion of last rituximab dose 28 TPO Agents Risk of thrombosis 29 Fostamatinib Potentially useful in COVID infections independent of platelet function 47 Immunomodulatory agents…”
Section: Rituximabmentioning
confidence: 99%